2015
DOI: 10.1111/bjdp.12097
|View full text |Cite
|
Sign up to set email alerts
|

Developmental change and cross‐domain links in vocal and musical emotion recognition performance in childhood

Abstract: Although the configurations of psychoacoustic cues signalling emotions in human vocalizations and instrumental music are very similar, cross-domain links in recognition performance have yet to be studied developmentally. Two hundred and twenty 5- to 10-year-old children were asked to identify musical excerpts and vocalizations as happy, sad, or fearful. The results revealed age-related increases in overall recognition performance with significant correlations across vocal and musical conditions at all developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 15 publications
1
24
2
Order By: Relevance
“…For example, Bouhuys and colleagues (1995) demonstrated that induced sad mood leads to an increased perception of sadness in ambiguous emotional expressions. Furthermore, there is some evidence for sex differences, with female children and adults being more sensitive to nonverbal emotion cues than male children and adults (e.g., Allgood & Heaton, 2015;Briton & Hall, 1995). With regard to verbal expression, research suggests that younger participants are more sensitive to emotional voices than older participants (Allen & Brosgole, 1993;Brosgole & Weisman, 1995;Kiss & Ennis, 2001;Orbelo, Grim, Talbott, & Ross, 2005;Paulmann, Pell, & Kotz, 2008).…”
Section: T Has Long Been Debated Whether and Tomentioning
confidence: 99%
“…For example, Bouhuys and colleagues (1995) demonstrated that induced sad mood leads to an increased perception of sadness in ambiguous emotional expressions. Furthermore, there is some evidence for sex differences, with female children and adults being more sensitive to nonverbal emotion cues than male children and adults (e.g., Allgood & Heaton, 2015;Briton & Hall, 1995). With regard to verbal expression, research suggests that younger participants are more sensitive to emotional voices than older participants (Allen & Brosgole, 1993;Brosgole & Weisman, 1995;Kiss & Ennis, 2001;Orbelo, Grim, Talbott, & Ross, 2005;Paulmann, Pell, & Kotz, 2008).…”
Section: T Has Long Been Debated Whether and Tomentioning
confidence: 99%
“…They observed a substantial increase in correct recognition with age, with only minor differences across emotion categories. More recently, Allgood and Heaton 48 used affect bursts, that is, short non-verbal vocal expressions such as laughter, weeping or scream 49 , 50 . They tested 228 children aged between 5 and 10 years and observed that 5- years old were significantly worse than 10-years old children when categorizing these stimuli as happy, sad or fearful.…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent study, they used meaningless sentences in different languages in a similar design and observed that early adolescents (age 11–13, n = 32) were not better than children (age 8–10, n = 25) at discriminating emotions, while they performed more poorly than adults (age 19–35, n = 22) 46 . Amongst these studies Allgood and Heaton 48 and Chronaki and et al . 27 observed a gender effect, consisting of better performance of females, albeit with apparently no interaction with age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations